Electrical and mechanical properties of Ta-N-Cu nanocomposite thin films - Wang, Chunmei (2008)
On the other hand, nanocomposite thin film shows many special and superior properties that can be used in numerous potential applications, since it is a multi-phase thin film. Nanocomposite thin films can be defined as the thin films that are composed of at least two different phases with one or more presenting in nano-scale. In this study, Cu phase acting as the second phase was incorporated into TaN matrix in order to tune the negative TCR of TaN. Experimental results show that annealed TaN thin films have a negative TCR (-850 ppm/ºC) while Cu films would normally give a positive TCR (+4300 ppm/ºC). It seems rather natural that TaN-Cu nanocomposite could demonstrate a near-zero TCR and the experiment result show that when proper Cu concentrations reach to 66 at.%~75 at.%, a zero-TCR could be obtained.